2006
DOI: 10.1111/j.1538-7836.2006.02120.x
|View full text |Cite
|
Sign up to set email alerts
|

Post‐treatment residual thrombus increases the risk of recurrent deep vein thrombosis and mortality

Abstract: Summary. Background: Recurrent thromboembolic events after an initial deep vein thrombosis (DVT) are relatively frequent. Residual thrombus in the affected veins on ultrasound scan at the completion of anticoagulant therapy has been described as a recurrence risk factor, and may have utility in stratifying those patients at risk. Objectives: The aims of the study were to correlate the risk of recurrence of DVT with the results of ultrasound at completion of oral anticoagulant therapy. A secondary aim was to re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
93
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(97 citation statements)
references
References 23 publications
(42 reference statements)
2
93
0
2
Order By: Relevance
“…It has been previously shown that a considerable number of recurrences can be seen in the opposite leg or present as PE [1,3,5]. Young et al [5] suggested that residual thrombus in DVT may be a marker for a generalized procoagulant diathesis.…”
Section: Discussıonmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been previously shown that a considerable number of recurrences can be seen in the opposite leg or present as PE [1,3,5]. Young et al [5] suggested that residual thrombus in DVT may be a marker for a generalized procoagulant diathesis.…”
Section: Discussıonmentioning
confidence: 99%
“…Young et al [5] suggested that residual thrombus in DVT may be a marker for a generalized procoagulant diathesis. Higher thrombogenic state of the patients may be the possible mechanism responsible for platelet activation and MPVand PDW elevation in patients with RVT [19][20][21].…”
Section: Discussıonmentioning
confidence: 99%
See 1 more Smart Citation
“…Sarasin and Bounameaux [38] calculated a theoretical recurrence rate of 0.9% per month after discontinuing anticoagulant therapy for proximal DVT, similar to annual recurrence rates of 7.0%-12.9% [39,40]. The risk of recurrent VTE is highest over the first 6-12 months after the index event, although cumulative rates can reach 24% at 5 years and 30% at 8 years after initial presentation [40][41][42][43]. The risk of recurrence is at least as great in the contralateral as in the ipsilateral extremity [42].…”
Section: ) Symptomsmentioning
confidence: 79%
“…While clinical factors such as obesity, 14 persistence of thrombosis following a conventional duration of anticoagulation, 15 use of graduated compression stockings, 16 and acute thrombolytic therapy 17 have each been established as outcome predictors with respect to PTS and/or recurrent VTE in adults, only thrombolytic therapy 13 and complete veno-occlusion 18 have been systematically studied and shown prognostic value within the framework of a cohort study or clinical trial of VTE in children. With regard to laboratory-based risk factors, as discussed in detail in this review, evidence has accumulated (albeit limited in some instances) for the association of potent inherited thrombophilia states (e.g., homozygous factor V Leiden or prothrombin polymorphisms, severe deficiency of intrinsic anticoagulants), persistent antiphospholipid antibodies (APA) and the APA syndrome (APAS), and markers of coagulation activation (specifically, elevated FVIII activity and D-dimer levels) with thrombotic outcomes such as PTS and recurrent VTE in children and/or adults.…”
Section: Introductionmentioning
confidence: 99%